DETERMINAN RETURN SAHAM DAN PERAN PEMODERASI INFLASI PADA INDUSTRI BARANG KONSUMSI DAN INDUSTRI DASAR KIMIA - Dede Misbah; Nurmala Ahmar; Adi Wiratno (Journal of Islamic Economy and Business (JIsEB), 2020)
The purpose from this research is to knowled factors take affect for stock return with using return on asset, earning per share, debt to equity ratio, current ratio, price to book value and inflation as moderation variabel. Used factor in this research are external factor respresented by inflation stage, and return on asset, earning per share, debt to equity ratio, current ratio, price to book value respresented by internal factor. The results showed that the consumer goods industry partially returns on assets, current ratio, price to book value and inflation significantly influence stock returns. While inflation can only moderate the influence between earnings per share, debt to equity ratio and price to book value on stock returns. In the basic chemical industry, the results of the study indicate that partially return on assets, earnings per share and current ratio significantly influence stock returns. While inflation can only moderate the effect of earnings per share on stock returns.